2009
DOI: 10.2353/ajpath.2009.090040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plasma From Muscle-Specific Tyrosine Kinase Myasthenia Patients on Regenerating Endplates

Abstract: Muscle-specific tyrosine kinase (MuSK) is essential for clustering of acetylcholine receptors (AChRs) at embryogenesis and likely also important for maintaining synaptic structure in adult muscle. In 5 to 7% of myasthenia gravis (MG) cases, the patients' blood contains antibodies to MuSK. To investigate the effect of MuSK-MG antibody on synapse regeneration, notexin was used to induce damage to the flexor digitorum brevis muscle. We administered aliquots of MuSK-MG patients' plasma to the flexor digitorum brev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Similarly, injection of MuSK-IgG into mice reduces the number of AChRs at the NMJ to 22% of controls, compromises the apposition of the presynaptic and postsynaptic components of the NMJ, 24 and reduces muscle contractility. 27 A recent report demonstrates that MuSK-IgG enhances internalization of MuSK from plasma membrane, which leads to progressive dispersal of postsynaptic AChRs by disruption of the MuSK scaffold and not by disruption of the agrin/LRP4/MuSK signaling pathway. 26 To summarize, MuSK-IgG does not reduce AChR expression in cultured cells, but active and passive immunization of model animals results in AChR deficiency, which is not likely due to blocking of the agrin/LRP4/MuSK pathway.…”
Section: In Vitro Plate-binding Assay Shows That Musk-igg Blocks Bindmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, injection of MuSK-IgG into mice reduces the number of AChRs at the NMJ to 22% of controls, compromises the apposition of the presynaptic and postsynaptic components of the NMJ, 24 and reduces muscle contractility. 27 A recent report demonstrates that MuSK-IgG enhances internalization of MuSK from plasma membrane, which leads to progressive dispersal of postsynaptic AChRs by disruption of the MuSK scaffold and not by disruption of the agrin/LRP4/MuSK signaling pathway. 26 To summarize, MuSK-IgG does not reduce AChR expression in cultured cells, but active and passive immunization of model animals results in AChR deficiency, which is not likely due to blocking of the agrin/LRP4/MuSK pathway.…”
Section: In Vitro Plate-binding Assay Shows That Musk-igg Blocks Bindmentioning
confidence: 99%
“…We found that even at 100 g IgG of control 2 or patient 2 did not block binding of LRP4 to MuSK ( figure 3B). DISCUSSION Molecular basis of MuSK-MG has been examined in cultured cells 30,31 as well as in active 28,29 and passive 24,26,27 immunization models. Application of MuSK-MG antibodies to TE671 muscle cells induces inhibition of cell proliferation and secondarily leads to downregulation of AChR and rapsyn.…”
Section: In Vitro Plate-binding Assay Shows That Musk-igg Blocks Bindmentioning
confidence: 99%
“…In some NMJs, there is misalignment between the presynaptic and postsynaptic portions of these synapses. The latter findings, some of which were also observed in the study of passive transfer of human AMM serum into mice 35 and in one of the three studies of AMM 40 , suggest that there is abnormal “signaling” between nerve terminal and muscle endplate in both directions resulting in failure of maintenance of the mature synapse in these animals 41 .…”
Section: Discussionmentioning
confidence: 71%
“…In addition, mice [76] and rabbits [77,78] immunized with domains of MuSK protein show less nAChR clustering at the NMJ and develop myasthenic symptoms, although it should be borne in mind that these immunization procedures elicit antibodies with the ability to activate complement, as anti-nAChR antibodies do, in contrast to human anti-MuSK antibodies that mostly lack this function (see below). Passive transfer of human anti-MuSK antibodies influences the activity of MuSK in regenerating endplates in mice, but without reducing MuSK levels, and thereby diminishes the size of the endplate affecting the functioning of AChRs [79]. Nevertheless, the exact pathways leading to disturbed neuromuscular transmission in MuSK-MG patients are still unclear and need further investigation.…”
Section: Antibodies Against Muskmentioning
confidence: 98%